Coinfection with Anaplasma phagocytophilum Alters Borrelia burgdorferi Population Distribution in C3H/HeN Mice - Holden, Kevin (American Society for Microbiology, 2005)
Borrelia burgdorferi, the agent of Lyme disease, and Anaplasma phagocytophilum, the agent of human anaplasmosis, are both transmitted by Ixodes sp. ticks and may occasionally coinfect a host. The population distributions of tick-transmitted B. burgdorferi infection were assessed using quantitative PCR targeting the flaB gene of B. burgdorferi in the ear, heart base, quadriceps muscle, skin, and tibiotarsal joint tissue of C3H mice previously infected with A. phagocytophilum. Population distributions of Anaplasma infection were assessed by targeting the p44 gene. A. phagocytophilum in blood and serologic response to both agents were evaluated. Spirochete numbers were increased in the ears, heart base, and skin of coinfected mice, but Anaplasma numbers remained constant. Antibody response to A. phagocytophilum, but not B. burgdorferi, was decreased in coinfected mice. These results suggest that coinfection with A. phagocytophilum and B. burgdorferi modulates pathogen burden and host antibody responses. This may be explained by the ability of A. phagocytophilum to functionally impair neutrophils, important cells in the early defense against B. burgdorferi infection.